Stegothesaurus - Heos, Bridget; McBeth, T.L (New York Henry Holt and Company, 2018)
Stegothesaurus has little in common with his fellow dinosaurs until he meets an allosaurus that seems as hungry for synonyms as he is.
Keywords: English language -- Juvenile fiction -- Synonyms and antonyms; Dinosaurs -- Juvenile fiction; English language -- Fiction -- Synonyms and antonyms; Stegosaurus -- Fiction; Allosaurus -- Fiction; Dinosaurs -- Fiction; Brothers -- Fiction